Tumor-Targeted Fluorescence Imaging and Mechanisms of Tumor Cell-Derived Carbon Nanodots - Taotao Huo; Wenshuai Li; Dong Liang; Rongqin Huang (MDPI AG, 2022)
An ideal cancer diagnostic probe should possess precise tumor-targeted accumulation with negligible sojourn in normal tissues. Herein, tumor cell-derived carbon nanodots (C-CNDU87 and C-CNDHepG2) about 3~7 nm were prepared by a solvothermal method with stable fluorescence and negligible cytotoxicity. More interestingly, due to the differences in gene expression of cancers, C-CND structurally mimicked the corresponding precursors during carbonization in which carbon nanodots were functionalized with α-amino and carboxyl groups with different densities on their edges. With inherent homology and homing effect, C-CND were highly enriched in precursor tumor tissues. Mechanistic studies showed that under the mediation of the original configuration of α-amino and carboxyl groups, C-CND specifically bound to the large neutral amino acid transporter 1 (LAT1, overexpressed in cancer cells), achieving specific tumor fluorescence imaging. This work provided a new vision about tumor cell architecture-mimicked carbon nanodots for tumor-targeted fluorescence imaging.